Communication Strategies For Sexual Violence Prevention and Handling In Higher Education on The Youtube Account of The Ministry of Education and Culture of The Republic Of Indonesia - Emi Salpiati (Publikasi Indonesia, 2024)
The research aims to determine communication strategies the Ministry of Education and Culture and Technology uses to prevent and handle sexual violence in universities on the YouTube channel Cerdas Berkarakter Kemdikbud RI. Using descriptive qualitative methods, the focus of research is to find communication strategies used based on elements of communicator, message, media, audience, and effect or result. The primary communicator is the Minister of Education and Culture, the highest leader. The target audience can be university leaders, lecturers, students, community leaders, religious leaders, mass media, and the general public. The effect is that there is controversy among netizens, as shown in comments that support and reject the policy. Another finding is that there was a selection of participation strategies in testimonial videos as support from representatives of various community groups showing the experience of participation as an equal in the process of different knowledge and skills.